Intraday Price And Volume Relations In The Stock And Warrant Markets - LIM, KOK SEE (2004)
This research paper examines the causal structure of price and volume in the warrant and stock markets within the Kuala Lumpur Stock Exchange (KLSE) of Malaysia. We investigate the intraday relations between price and trading volume of the top 25 most active warrants and their underlying stocks during the period from 24th September to 16th December 2003. The data were grouped into 5-minute intervals for this study. Unit root, cointegration, vector error correction (VEC) and Granger causality tests were used to analyse the lead-lag between price and volume of the warrant and stock markets.